2021
DOI: 10.1186/s12985-021-01687-w
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of interleukin-38 exacerbates coxsackievirus B3-induced acute myocarditis in mice

Abstract: Background Interleukin (IL)-38, a novel member of the IL-1 family, has been reported to be involved in several diseases associated with viral infection. However, the expression and functional role of IL-38 in acute viral myocarditis (AVMC) have not been investigated. Methods Male BALB/c mice were treated with intraperitoneal (i.p.) injection of coxsackievirus B3 (CVB3) for establishing AVMC models. On day 7 post-injection, the expression of IL-38 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In sepsis mice model, the level of IL‐38 increased and IL‐38 could prolong the survival of mice. 53 Xue et al 54 demonstrated that the neutralization of IL‐38 exacerbated coxsackievirus B3‐induced viral myocarditis (AVMC) in mice, possibly due to a Th1/Th17 cell imbalance and elevated virus replication. These findings indicate that IL‐38 plays a protective role during pathogen infection and is a potential therapeutic target for infectious diseases.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…In sepsis mice model, the level of IL‐38 increased and IL‐38 could prolong the survival of mice. 53 Xue et al 54 demonstrated that the neutralization of IL‐38 exacerbated coxsackievirus B3‐induced viral myocarditis (AVMC) in mice, possibly due to a Th1/Th17 cell imbalance and elevated virus replication. These findings indicate that IL‐38 plays a protective role during pathogen infection and is a potential therapeutic target for infectious diseases.…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…In addition, neutralizing IL-38 antibodies significantly exacerbated heart failure and significantly increased mortality in mice with myocarditis, and further study of the mechanism revealed that this may be achieved through inhibition of th17 cell differentiation. 51 Secondly, Wei et al reported that, in the anterior descending ligation mouse model, the level of IL-38 was significantly elevated. However, exogenous supplementation of IL-38 significantly improved cardiac ejection function and inhibited cardiac remodeling in mice, the underlying mechanism may be the inhibition of dendritic cell hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of IL‐38's acute role in response to local or systemic infections, however, is scarce. In mice infected with coxsackievirus B3, neutralization of IL‐38 reduced survival and cardiac function and was associated with increased viral replication 26 . In murine models of sepsis, IL‐38 administration decreased inflammatory cytokines and organ damage and augmented bacterial clearance 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In mice infected with coxsackievirus B3, neutralization of IL‐38 reduced survival and cardiac function and was associated with increased viral replication. 26 In murine models of sepsis, IL‐38 administration decreased inflammatory cytokines and organ damage and augmented bacterial clearance. 27 In humans, IL‐38 plasma concentrations were elevated in patients with sepsis, which negatively correlated to circulating proinflammatory cytokines and blood leukocyte counts.…”
Section: Introductionmentioning
confidence: 99%